(untitled) - Bernacki, Ed (New York, 2002)
This is a book for business owners,managers,professionals and team leaders who want to create a more competitive business that is profitable,successful and a leader.
Keywords: Business intelligent,Business in successful,New products,Bí quyết kinh doanh,Thành công trong kinh doanh